Researching Context-Aware Recommendation Systems in Mobile Environments - Rodríguez-Hernández, María del Carmen; Ilarri, Sergio (Jornada de Jóvenes Investigadores del I3A, 2017)
The design and implementation of generic frameworks to support an easy development of context-aware recommendation systems has been relatively unexplored. In this paper, we briefly present our ongoing work for the definition of a framework that will support the development of context-aware recommendation systems in distributed and mobile environments. Those systems will allow suggesting relevant items to mobile users.